A Study on the Use of Computerised Accounting Systems in Small Business: A Case of Small Business in Libya - Saleh, Saleh Abdullah (2011)
The main objective of this research is to examine the relationship between perceived usefulness, ease of use and computerized accounting system (CAS). This study is designed to examine the usage of will computerize accounting system (CAS) to ascertain if there are any issues faced by small business in Tripoli, Libya. In addition the behavioral and performance changes of technology acceptance among small business in Tripoli, Libya were investigated. Libyan small companies need to be cost effective and timely in their accounting practices and these could not be achieved with its traditional way of accounting reporting. CAS is meant to conduct the company’s operations and activities, and providing information concerning the variety of users’ interest. Indeed, it is the combination of human interaction and technology that could be employed to meet excellent and efficient operation that was lacking in these small business companies. To achieve these objectives, quantitative method of data collection was employed. This involved the use of questionnaire to gather information from the sample of 100 Libyan employees resident in Malaysia. However, the response rate was 48%. The results of the study indicate that a positive association between perceived usefulness and intention to use CAS was supported. This study has critically reviewed the approached that makes the computerized accounting system more reliable and efficient, from the previous studies. The aim here is to learn more about the influence and role played by accountant in their decision through computerized accounting system. The integrated approach which helps the accountants to develop and understand accounting base issues after using CAS and review of CAS utilization for small business in Tripoli, Libya to encourage management and accountant for their efficiency in business record keeping were focused.